THE RIGHTS OF FOREIGN TOURISTS IN IRANIAN LEGAL SYSTEM REGARDING THE PUBLIC ECONOMIC LAW - Ghafari, Hoda (ВЕСТНИК ЧЕЛЯБИНСКОГО ГОСУДАРСТВЕННОГО УНИВЕРСИТЕТА; № 3(449) (2021): Вестник Челябинского государственного университетаDO - 10.47475/1994-2796-2021-10323, 2022)
The Global Codes of Tourism Ethics were developed by The United Nations with the aim of improving the tourism industry and building international memorandum and also achieving sustainable development and preserving tourism heritage. These codes above all emphasize on tourism rights as a platform for the development of the tourism industry as a basic institution of Economy. Therefore, the comparative survey of these codes with the laws of the country and determination of its legal capacity is necessary to compile such codes. the development of the Iranian Tourism and Tourism Industry Act adopted in October 2008 and its implementing regulations provide some privileges for tourists, including Personal or direct privileges and indirect privileges in order to creating the appropriate tourism platform. In this article, we intend to survey the capa